Integrating Ethnobotany and Indigenous Knowledge into Higher Education Curricula: Insights from a Global Biobliometric Analysis - Marsandi, Fenky; Sutadji, Eddy; Kuntadi, Iwa; Rizal, Fahmi; Nur Rahma, Andika Bagus; Fajri, Hidayatul (Ethnobotany Research and Applications, 2025)
Background: Indigenous knowledge and ethnobotany are essential to preserving ecological sustainability, biodiversity, and cultural heritage. Its inclusion in higher education curricula is still somewhat limited, despite its significance. In order to preserve cultural identity and address global issues, it is imperative that traditional knowledge be included into academic frameworks as the demand for sustainable education grows. Methods: To investigate global trends in incorporating ethnobotany and indigenous knowledge into higher education curricula, this study uses bibliometric analysis. VOSviewer and Biblioshiny were used to evaluate data gathered from the Scopus database (1997–2024) in order to find new research themes, collaborative networks, and publication trends. Results: In response to the sustainable development goals, ethnobotany and the integration of indigenous knowledge have garnered a great deal more scholarly attention, especially after 2010. As a global leader, Indonesia contributes the most citations and publications. Network analysis emphasizes how important local knowledge is in building context-sensitive and transdisciplinary teaching methods, which promotes curriculum design innovations. Conclusions: There is revolutionary potential for sustainable education when ethnobotany and indigenous knowledge are included into higher education. This integration is a calculated step toward creating innovative teaching practices that are globally adaptive and culturally appropriate. Keywords: Ethnobotany, Indigenous knowledge, Higher education, Curriculum, Bibliometric analysis